2012
DOI: 10.1371/journal.pone.0036135
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of Rabbit Retina with Retinal Degeneration by Using Spectral-Domain Optical Coherence Tomography

Abstract: BackgroundRecently, a transgenic rabbit with rhodopsin Pro 347 Leu mutation was generated as a model of retinitis pigmentosa (RP), which is characterized by a gradual loss of vision due to photoreceptor degeneration. The purpose of the current study is to noninvasively visualize and assess time-dependent changes in the retinal structures of a rabbit model of retinal degeneration by using speckle noise-reduced spectral-domain optical coherence tomography (SD-OCT).Methodology/Principal FindingsWild type (WT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
0
45
0
3
Order By: Relevance
“…Total retinal thickness (from inner limiting membrane to Bruch membrane) in rd10 mice was measured using volume scan images33 within a circle 0.366 mm in diameter, the center of which was adjusted to the center of the optic nerve head. The mean value of the upper and lower quadrant was averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Total retinal thickness (from inner limiting membrane to Bruch membrane) in rd10 mice was measured using volume scan images33 within a circle 0.366 mm in diameter, the center of which was adjusted to the center of the optic nerve head. The mean value of the upper and lower quadrant was averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Ophthalmic examinations such as optical coherence tomography (OCT), electroretinography (ERG), and visual acuity testing are able to detect visual function and inner and outer nuclear layer thickness (Berson et al, 1996; Lim et al, 2008). Advances in in vivo imaging systems, such as adaptive optics scanning laser ophthalmoscopy (AOSLO) and spectral domain OCT (SD-OCT), allows for the monitoring of retinal lamination, oxygenation in blood vessels, cellular changes, progression of disease, and response to treatments (Bizheva et al, 2006; Freeman et al, 2010; Holmgren, 1865; Huang et al, 1991; Huber et al, 2009; Kagemann et al., 2007; Muraoka et al, 2012; Novais et al, 2016; Pron, 2014; Srinivasan et al, 2007; Toth et al., 1997; Zayit-Soudry et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…An SD-OCT system (Bioptigen Spectral Domain Ophthalmic Imaging System; Bioptigen, Inc., Durham, NC, USA) was used to assess the retinal health post-intravitreal injection in each rabbit at the specified time periods. OCT evaluation allows for noninvasive detection of retinal architecture, including quantitative measurements of retinal thickness and longitudinal observation of the retinal architecture (27). OCT examination demonstrated that the structure of retina was intact and there was no difference in the retina after intravitreal injection.…”
Section: Clinical Exams For Safety Estimationmentioning
confidence: 99%